Penatalaksanaan fisioterapi pada kondisi post fraktur colles dextra di r.s pku muhammadiyah surakarta - Afenti, Aryunistya; , Dwi Kurniawati, SSt.FT (2013)
Background : Injury to the wrist called Colles fracture most often occurs in older people who fall resting on the palm of the hand to hand in dorsal flexion position. Usually found clinically typical deformity called a forks. Problems statements : How about physiotherapy treatment with infred modalities, and massage, can reduce pain in cases of post Colles fracture dextra, as well as with exercise therapy canimprove muscle strength and increase range of motion in the right wrist? Objectives : To know the implementation modalities of physiotherapy with infrared, massage, and exercise therapy to decrease pain, increase range of motion, and increase muscle strength in the case of post fracture colles dextra. Result : After therapy for six times in getting the result to the reduction of tenderness of T1 : 3 (mild pain) be T6 : 2 (very mild pain) and the motion of the pain T1 : 5 (pain servere enough) be T6 : 3 (mild pain), an increase in muscle strength in dorsal flexion movement of T1 : 3 be T6 : 4, palmar flexion of T1 : 3 be T6 : 4, ulnar deviation of T1 : 3 be T6 : 4, and radial deviation of T1 : 3 be T6 : 4, and an increase in range of motion in the sagital and frontal T1 = S : 150-0-200 be T6 = S : 250-0-350 and T1 = F : 50-0-200 be T6 = F : 150-0-300 , whereas LGS passive dextra wrist in the sagital and frontal also increase the T1 = S : 150-0-250 be T6 = S : 250-0-350 and T1 = F : 50-0-200 be T6 = F : 150-0-300. Conclusions : Infrared (IR) and Massage can reduce pain and joint stiffness because of they give the effect of relaxation on the condition of post fracture Colles dextra, therapy active exercise can increase the strength muscle and improve the range of motion (LGS) on condition post fracture Colles dextra.